Expression of Love for Ahl Al-Bayt in Acehnese Society - Lukman Hakim; Syamsul Rijal (Al-Albab, 2021)
Theologically, the Acehnese ordain themselves as loyal followers of Sunni Islam, but there are Shi’a elements in their culture. To date, there are some traditions of expressing love for the Ahl al-Bayt (Prophet Muhammad’s family) which is one of the main characteristics of the Shi'a. This research is based on the hypothesis that several cultural practices in Aceh contain Shi’a elements. This study seeks to reveal the cultural practices of the Sunni followers in Aceh in expressing their love for the Ahl al-Bayt. This study uses a qualitative approach with a descriptive analysis method from a combination of library and field data. This study found that, historically, the acculturation process of Shi'a culture into the Sunni followers in Aceh has coincided with the process of the arrival of Islam in the Indonesian Archipelago. This is possible given the position of Aceh in the history of Islamization in the Indonesian Archipelago. This acculturation has left traces of culture inspired by Shi’a such as the tradition of Ashura porridge, Boh Husayn cake. All these traditions have been preserved because these Shi'a values contain expressions of love for the Ahl al-Bayt who also have a place in the hearts of the Sunni adherents in Aceh.